2012
DOI: 10.1002/aic.13808
|View full text |Cite
|
Sign up to set email alerts
|

Spatial reaction engineering approach as an alternative for nonequilibrium multiphase mass‐transfer model for drying of food and biological materials

Abstract: in Wiley Online Library (wileyonlinelibrary.com).Drying is a complex process which involves simultaneous heat and mass transfer. Complicated structure and heterogeneity of food and biological materials add to the complexity of drying. Drying models are important for improving dryer design and for evaluating dryer performance. The lumped reaction engineering approach (L-REA) has been shown to be an accurate and robust alternative for cost-effective simulations of challenging drying systems. However, more insigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 59 publications
2
29
0
Order By: Relevance
“…At the end of drying, the gradient was not noticeable which indicated that the equilibrium condition was nearly attained. Similar profiles were also observed during drying modelled using the spatial reaction engineering approach (S-REA) 25,28,34 . For the temperature profiles, as shown in Figure S2, there was no noticeable gradient of temperature during drying.…”
Section: Mathematical Modellingsupporting
confidence: 56%
See 2 more Smart Citations
“…At the end of drying, the gradient was not noticeable which indicated that the equilibrium condition was nearly attained. Similar profiles were also observed during drying modelled using the spatial reaction engineering approach (S-REA) 25,28,34 . For the temperature profiles, as shown in Figure S2, there was no noticeable gradient of temperature during drying.…”
Section: Mathematical Modellingsupporting
confidence: 56%
“…For modelling water removal from the droplet during drying, the mass balance of water can be represented as 25 : The heat balance can be written as 25 :…”
Section: Mathematical Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…2-7 show that the S-REA is accurate to model drying of non-food materials. Previously, the S-REA was implemented to describe drying of food and biological materials and the results of modeling match very well with the experimental data (Putranto and Chen, 2013a). The accuracy of the S-REA may be because of the applicability of the REA to describe the local evaporation/condensation rate.…”
Section: 1mentioning
confidence: 91%
“…Among a series of equations tested, the one that provides a value consistent with the literature is that proposed by Putrano and Chen [8]:…”
Section: Diffusivity Estimationmentioning
confidence: 83%